Mauritius : Financial Sector Assessment - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) is the joint IMF-World Bank work, based on the context of the Financial Sector Assessment Program (FSAP), intended to identify strengths, and vulnerabilities, as well as development needs of the financial sector. The report thus summarizes main findings, and policy recommendations as follows. Mauritius has been remarkably successful in achieving rapid growth, and substantial diversification of a formerly mono-agricultural economy. However, maintaining the past high rates of growth, and employment will pose a major challenge. The trade preferences on which two of the pillars of the economy are founded are being eroded, forcing the sugar and textile industries, to significantly improve their competitiveness, or lose market share to larger, lower-cost producers. In partnership with the private sector, the government is taking decisive measures to build a knowledge economy based on higher value-added services, notably in information and communication technologies. They have also adopted programs to modernize, and improve competitiveness in the sugar and textile industries, and, are investing heavily in education, in order to realign the labor force with the requirements of the new engines of growth. Mauritius has a relatively large and well-developed domestic financial system, and a growing offshore sector, however, the country needs to further diversify its financial sector, namely within the banking system. This includes continuing the strengthening of banking supervision, fostering the development of alternatives to bank lending to reduce portfolio concentrations, and increase competition. Additionally, there is the need to encourage sound international risk diversification, by strengthening provisioning levels, so as to enhance the resilience of the system to a downturn in economic activity, and, by reducing the government's implicit contingent liability in the banking system.